Qualitative Description Study Of Midwife's Expectations In Care Of Hiv-Positive Mothers In Pregnancy, Partnership And Postborn - Sri Wahyuni; Nur Fitriana Iriyani (JKM (Jurnal Kebidanan Malahayati), 2022)
Latar belakang Jumlah Penderita HIV terus meningkat di setiap negara termasuk Indonesia. Provinsi Papua adalah  provinsi dengan jumlah temuan kasus HIV ketiga  di Indonesia. Dari bulan Januari- Juli 2020 dari Ruang VCT dan Klinik Kebidanan didapatkan 50 kasus Ibu hamil datang Ke RSUD Jayapura dengan HIV positif dalam masa kehamilan, persalinan, dan NifasTujuan Untuk mengetahui harapan bidan dalam merawat ibu dengan HIV Positif dalam masa kehamilan, persalinan, dan nifas di RSUD Jayapura.Metode deskriptif kualitatif  penelitian ini merupakan penelitian deskriptif kualitatif. Partisipan sejumlah 12 bidan dan 3 pasien HIV positif yang dipilih dengan menggunakan Purposive Sampling dengan kriteria bidan tersebut bekerja minimal 1 tahun di RSUD Jayapura, bersedia menjadi partisipan dan memiliki pengalaman perawatan ibu dengan HIV baik pada masa kehamilan, persalinan, maupun nifas. Pengumpulan data dengan wawancara mendalam. Analisa Data dengan Content Analysis.Hasil harapan Bidan dan pasien HIV dalam perawatan ibu dengan HIV positif adalah tidak ada lagi penularan HIV dari ibu ke bayi, semoga tidak ada luka infeksi post operasi SC pada ibu nifas dengan HIV, penyuluhan dari pihak puskesmas lebih banyak dan pro aktif untuk mencegah penularan HIV, terus ada update ilmu bagi bidan dalam penanganan HIV terbaru, adanya penambahan atau regenerasi konselor HIV di RSUD Jayapura, Stigma dan Diskriminasi Segera hilang, tidak ada yang menutup status dari petugas Kesehatan, suami, maupun keluarga.Kesimpulan: harapan bidan adalah supaya tidak ada lagi penularan HIV dari ibu ke bayi, adanya regenerasi konselor HIV di RSUD Jayapura, tidak ada lagi pasien yang menutup status dari petugas Kesehatan, dan penyuluhan dari puskesmas tentang pencegahan lebih banyak.Saran: Sebaiknya rutin diadakan regenerasi konselor HIV di rumah sakit dan diperbanyak progaram penyuluhan tentang pencegahan HIV oleh tim dari Dinas Kesehatan. Kata Kunci: bidan, harapan, perawatan HIV ABSTRACT Background and Objectives, the number of people with HIV continues to increase in every country including Indonesia. Papua province is the province with the third number of HIV cases in Indonesia. From January to July 2020 from VCT room and midwifery clinic, 50 cases of pregnant women came to Jayapura Hospital with HIV positive in pregnancy, childbirth, and Nifas. To find out the hopes of midwives in caring for mothers with HIV Positive in pregnancy, childbirth, and postpartum at Jayapura Hospital.Pupose  method is qualitative descriptive research. Participants of 12 midwives and 3 HIV positive patients were selected using Purposive Sampling with the criteria of the midwife working for at least 1 year in Jayapura Hospital, willing to be participants and have experience of maternal care with HIV both during pregnancy, childbirth, and postpartum. Data collection with in-depth interviews. Data Analysis with Content Analysis.Results of the study hope that midwives and HIV patients in the care of mothers with HIV positive is that there is no more mother-to-baby transmission of HIV, hopefully there are no postoperative SC infection wounds in mothers with HIV, counseling from the health center more and pro-active to prevent HIV transmission, there continues to be science updates for midwives in the latest HIV treatment,  The addition or regeneration of HIV counselors in Jayapura Hospital, Stigma and Discrimination Soon disappeared, no one closed the status of health workers, husbands, or families.Conclusion of the midwife's hope is that there will be no more mother-to-baby HIV transmission, the regeneration of HIV counselors in Jayapura Hospital, no more patients who close the status of health workers, and counseling from health centers about prevention more.Suggestion: It is better to regularly regenerate HIV counselors in hospitals and multiply the counseling program on HIV prevention by a team from the Health Service. Keywords: HIV treatment, hope, midwife.